0676 Prevalence And Clinical And Polysomnographic Variables Associated With Periodic Limb Movements In Sleep (PLMS) In Patients With OSA. (27th April 2018) - Budhiraja, R; Javaheri, S; Epstein, L J; Pavlova, M; Batool-Anwar, S; Johnsen, J H; Quan, S F
Abstract: Introduction: We aimed to assess the prevalence and clinical and polysomnographic variables associated with PLMS in patients with OSA in Apnea Positive Pressure Long-term Efficacy Study (APPLES), a prospective 6-month multicenter randomized controlled trial with 1105 subjects with OSA. Methods: All participants underwent a polysomnogram (PSG). The apnea hypopnea index (AHI), total sleep time (TST), Sleep Efficiency (SE), Sleep Onset Latency (SOL), arousals and PLM Index (PLMI) were computed. Results: Of all subjects, 19.7% of the participants had PLMI ≥ 10/hour, 14.8% had PLMI ≥ 15/hour, 12.1% had PLMI ≥ 20/hour and 7.5% had PLMI ≥ 30/hour. The 75 th percentile PLMI was 5.5, 80th percentile was 9.3, 90th percentile was 24.1 and 95th percentile was 37.2/hour. PLMI was associated positively with SOL (R=.075, P=0.01) and inversely with SE (R=-.113, P=<0.001) and TST (R=-.106, P=<0.001). Linear regression models showed that the association between PLMI and sleep variables was independent of AHI and depression (HAMD score). There was no significant correlation between PLMI and AHI, Epworth Sleepiness Scale scores or Maintenance of Wakefulness Test sleep latency. No correlation was seen between PLMI and Hamilton Depression Rating Scale (HAMD) or Sleep Apnea Quality of Life Index (SAQLI) scores. A linear regression model showed increasing age (Beta=.19, P<0.01) and total caffeine servings per week (Beta=.09, P=0.02) to be independent predictors of PLMI. A logistic regression model showed higher odds of PLMI ≥ 10 with older age (OR=1.03, P<0.001), male gender (OR=1.63, P=0.01), antidepressant use (OR=1.48, P=0.048), and caffeine servings per week (OR=1.01, P=0.04). In comparison with those with PLMI<10, those with PLMI ≥ 10 had lower AHI (37.3 ± 20.6 vs 40.7 ± 26.2, P=0.04), lower SE (75.8 ± 13.2% vs 78.8 ± 12.5%, P=0.02) and TST (364.6 ± 66.9 vs 379.3 ± 64.7 minutes, P=0.003), higher arousal index (32.2 ± 20.6 vs 28.7 ± 20.4/hour, P=0.03) and a tendency towards higher SOL (21.8 ± 25.9 vs 18.3 ± 20.9 minutes, P=0.06). Conclusion: This study confirms a high prevalence of PLMS in patients with OSA. PLMI was associated with worse sleep quality but not excessive daytime sleepiness. Support (If Any): NHLBI contract 5UO1-HL-068060.